Three-Point Boundary Value Problems for Conformable Fractional Differential Equations - H. Batarfi; Jorge Losada; Juan J. Nieto; W. Shammakh (Journal of Function Spaces)
We study a fractional differential equation using a recent novel concept of fractional derivative with initial and three-point boundary conditions. We first obtain Green's function for the linear problem and then we study the nonlinear differential equation.